Neticle Technologies - Gass, Daniel F.; Su?di, Anna Fruzsina; Koning, Rosanne; Liu, Che; Hulsink, Willem (London : SAGE Publications Ltd, 2017)
Neticle is social listening and business intelligence tool based on sentiment analysis technology. Developed by a team of four from Hungary, the software offers some exclusive features and superior accuracy in social listening for Hungarian language content. The company, Neticle Technologies, has grown rapidly since attracting its first paying customer in February 2013. It had 54 corporate customers and 10 employees by the end of 2014, acquired mainly through organic growth. After becoming the market leader in Hungary, the issue of future growth was brought into the schedule of discussions.For the next step of growth, Neticle can either enter another geographical area or extend its product portfolio. Both options provide great opportunity but also present certain risks. Because of resource constraints, Neticle founders feel they should prioritize and focus on one approach at a time. Pe?ter Szekeres and his team need to make the decision on which step to take first: product line expansion or internationalization.
Originally Published InGass, D. F., Su?di, A. F., Koning, R., Liu, C., & Hulsink, W. (2015). Neticle Technologies. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Neticle Technologies -- Case studies; Strategic planning -- Case studies; Globalization -- Case studies